Oralidade na sala de aula: uma proposta didática para o sétimo ano do ensino fundamental - Mello, Maria de Fátima de (2016)
This research aims to provide a reflection on oral language in the teaching/learning process in the school drawing on the oral and written production in the classroom. It proposes an education strategy which involves a set of activities to promote the production of oral and written texts, such as news and interview for a school radio broadcast. The set of activities comprised a total of 16 classes divided into two modules: Module 1 focused on activities related to the genre radio news. Module 2 focused on spoken language practices in conducting interview and expressively reading news and poems, while also becoming aware of prosody aspects, such as intonation and pause. Finally, students produced and broadcasted a program on the school radio. All participants attended the 7 th grade of a public school in Valparaíso de Goiás, state of Goiás, Brazil. The theoretical foundation drew on: Bakhtin (2011) and Schneuwly and Dolz (2013) on discursive genres; Lage (2006), Ferraretto (2001) and Baltar (2012) on radio news and interview genres; Marcuschi (1997, 1999, 2001, 2008), Fávero et al (1999) and Crescitelli and Reis (2014) on oral and written language. All students’ outputs were submitted to data analysis.The results indicated that as students performed spoken and written activities, their engagement and attitude toward school themes became more visible. This contributes to increasing students’ communicative and discursive competence and to engaging them in Portuguese Language classes.